Effect of milling time on powder's structure evolution of Ti(C, N)-304 stainless steel cermet. (16th March 2018) - He, Lin; Gao, Yimin; Li, Yefei; Liu, Zhiwei; Huo, Xuxu; Zhai, Wenyan
Abstrcat: In this paper, Fe, Ni, Cr, Mn, Si, C element powders and Ti(C, N) ceramic powder were used as starting materials to fabricate Ti(C, N)-304 stainless steel cermet via high-energy ball milling in argon atmosphere. Effect of milling time on powders' structure, including morphology of powder, average grain size, dislocation density and the solid solubility of Cr in Fe, were studied by x-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). XRD pattern shows that mechanical alloying was occurred during high energy ball milling. Nickel and chromium were gradually solid dissolved into iron and formed 304 stainless steel (304 s), the maximum solid solubility of Cr in Fe is 16.8 at.% obtained at 18 h. The mean grain size of Ti(C, N) particles and 304 s grains declined before 14 h and the minimum grain size of them were about 20 nm and 250 nm respectively, which is consistent with the results revealed by TEM images. The dislocation density in stainless steel powder increased with increasing milling time. After the powders were milled for 18 h, the cermet sintered at 1450 °C for 1 h has the maximum hardness (83.7 HRA) and relative density (93.3%).